55.1k views
0 votes
3х - у = 6
6х + y = 21

User Myndex
by
5.0k points

2 Answers

5 votes

Answer:

(3, 3 )

Explanation:

Given the 2 equations

3x - y = 6 → (1)

6x + y = 21 → (2)

Adding (1) and (2) term by term will eliminate the term in y, that is

(6x + 3x) + (y - y) = (21 + 6)

9x = 27 ( divide both sides by 9 )

x = 3

Substitute x = 3 into either of the 2 equations and solve for y

Using (2), then

(6 × 3) + y = 21

18 + y = 21 ( subtract 18 from both sides )

y = 3

Solution is (3, 3 )

User Lanny
by
5.5k points
3 votes

Answer:

y=3 x=3

Explanation:

use substitution method :

3x-y=6-------(1)

6x+y=21------(2)

from (2),

6x+y=21

y=21-6x------(3)

substitude (3) inside (1)

3x-y=6

3x-(21-6x)=6

3x-21+6x=6

9x=27

x=3

if x = 3

from (1),

3x-y=6

3(3)-y=6

9-y=6

-y=-3

y=3

User Maantje
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.